Constraints on the operation of a DI diesel engine in partially-premixed combustion mode - Keeler, Benjamin (2009)
Partially-premixed Charge Compression Ignition (PCCI) combustion is defined by increased levels of premixed charge whilst retaining control over combustion through injection timing. An experimental investigation has been carried out on a current generation DI diesel engine, equipped with High Pressure Common Rail (HPCR) fuel injection equipment and an external Exhaust Gas Recirculation (EGR) system. The aims of the investigation were to determine the constraints imposed on operating a PCCI combustion strategy with the aim of simultaneously reducing engine-out net soot and NOx emissions.